SELECTED EXCIPIENTS IN ORAL SOLID DOSAGE FORM WITH DRY EXTRACT OF PYROLA ROTUNDIFOLIA L. - DARZULI, NATALIA; BUDNIAK, LILIIA; HROSHOVYI, TARAS (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the present study was to select excipients in an oral solid dosage form with a dry extract of round-leaved wintergreen (Pyrola rotundifolia L.) by using asymmetric, rotatable composite plan of the second-order (uniform plan No. 17). Methods: The tablets were prepared by using a direct compression method. The most important pharmaceutical factors selected were considered in more details at developing the optimal composition and technology of the studied tablets of the round-leaved wintergreen extract. Each one was studied at five levels using asymmetric, rotatable composite plan of the second order. Results: Increasing amounts of PROSOLV® EASYtab SP and croscarmellose sodium in the powder mass, its flowability decreases, and increasing amounts of Tablettose® 80 improves flowability. Increasing the amount of Tablettose® 80 in the tablets composition leads to improved uniformity. The strength of the tablets increased with increasing amounts of Neusilin® US 2 at different combinations of levels of the other three factors. When studying the effect of the amounts of croscarmellose sodium on the disintegration of tablets, it was found that the best disintegration values were obtained in the study of croscarmellose sodium at the upper level. Conclusion: Oral solid dosage form with dry extract of round-leaved wintergreen was successfully prepared by the direct compression method. The optimal composition of tablets was determined by the regression analysis.